Should the HPV positive oropharyngeal cancer patient be considered for a two-stage dental assessment for their radiation treatment?. (November 2021) - Patel, Vinod; Kwok, Jerry; Burke, Mary; Urbano, Teresa Guerrero; Fenlon, Michael
Highlights: Oropharyngeal cancer patients are at increase risk of osteoradionecrosis. HPV positive oropharyngeal cancer present with a complex dentition. A two stage dental assessment considered radiation dose and tumour response. Abstract: Patients due to commence head and neck radiation treatment are expected to undergo a dental assessment and be deemed 'dentally fit'. Though this intervention is welcomed by the dental fraternity it is not without its challenges especially in human papilloma virus (HPV) related oropharyngeal cancer (OPC) which has seen a phenomenal rise over the past decade. This perspective piece presents these challenges and proposes a potential adaption of the dental assessment for HPV OPC patients though not necessarily exclusive to this tumour sub-site.